Caetitus gen. nov.: a new genus of Neotropical Copiphorini (Tettigoniidae: Conocephalinae: Copiphorini) to include C. porteri (Bolivar, 1903) - Antunes, André Fonseca; Takiya, Daniela Maeda; Chamorro-Rengifo, Juliana (Zootaxa, 2018)
Daedalellus porteri (Bolivar, 1903) was described based on a single broken female holotype collected in an undetermined locality in Brazil. This species is herein redescribed based on two males and one female collected in Caetité, Bahia State, Brazil, including its morphology of fastigium and male terminalia. Based on comparisons to other Daedalellus species and Neotropical Copiphorini genera, the new monotypic genus Caetitus gen. nov. is herein proposed. Caetitus porteri comb. nov. differs from species of Daedalellus and other related genera, such as Panacanthus, Copiphora, Borinquenula, and Lirometopum, mainly due to differences of the fastigium and male external terminalia.